(untitled) (European Journal of Social Sciences, 2018)
Albania has always aspired to be part of the European family and for this purpose has constantly experienced different challenges. EU has monitored Albanian progress and in each case has provided its recommendations. Since the signature of the Stabilization and Association Agreement, one of the main challenges that Albania had to face was justice reform and fight against corruption and organized crime, which of course were closely related to each other. A great number of international organizations have been present in Albania, providing expertise and support to achieve the integration key priorities among which one of the most important was the justice system. However corruption and incompetence were very spread among prosecutors and judges. Consequently, following the insistence of international actors as well as the increased awareness of local actors, it was concluded that a deep reform in justice was necessary, which would finally clear justice system and would enable it to perform its task of doing justice. As rare as ever, with the unanimous vote of all Albanian parliamentarians, the constitutional changes were approved and additional laws for the reform in justice were adopted too. This legal package initially included asset assessment, a background assessment and a proficiency assessment and then the regulation of the procedure of appointment, disciplinary measures and control during the assignment, and the verification of complaints, for each judge and prosecutor in Albania. This reform is expected to open Albanian road toward EU integration.